PUBERTY IN ADOLESCENT GIRLS - Syafira Idza Fatahunnisa; Annisa Paramitha; Abib Azkan; Rizqullah Zaki; Huga Al Falih (PT. Radja Intercontinental Publishing, 2025)
Puberty is a complex transitional phase from childhood to adulthood, characterized by significant physical, psychological, and social changes. In adolescent girls, puberty involves the maturation of reproductive organs, breast development, the onset of menstruation (menarche), and changes in body fat distribution. Besides biological changes, emotional shifts such as anxiety, embarrassment, and identity-seeking also occur. This study employs a literature review method using various journals related to puberty to examine the impact of these changes on adolescent adjustment. The findings indicate that a lack of knowledge and family support is associated with increased anxiety, stress, and negative self-concept among adolescent girls. Therefore, reproductive health education and family involvement are essential in helping adolescents adapt to puberty in a healthy manner.